Brain predomination and academic performance in the students of the education faculty of the National University of Altiplano (UNA) –Puno - Myrna Cleofé Sánchez Rossel (2020)
The he not very optimal level of performance and the lack of awareness about the predominance of the brain, within the teaching-learning process, was what motivated this study; The objective of which was to determine the relationship between brain dominance and academic performance of students from the UNA-Puno Faculty of Education Sciences, during the 2019-I semester. The descriptive-correlational design was used, framed in the non-experimental type of research and in the quantitative approach. The sample (stratified and proportional, based on the random method) was made up of 305 students; those that were evaluated with the instruments: Developer of the tricerebral quotient, to measure the cerebral predominance and the Documentary Record Card for academic performance. At the end of the investigation, it was identified that the predominant brain is the right, with a frequency that represents 52%. Likewise, the level of academic performance is good, with a frequency that represents 49%. This allowed obtaining as a result a value of r = 0.321, which corresponds to a moderate relationship between the variables, confirming the hypothesis. Thus, it is concluded that cerebral predominance and academic performance are moderately associated.